A production method of a flexible copper-clad laminate and a peelable copper foil with a carrier
By pretreating the polymer film and sinking the active thin copper layer, forming a barrier layer and a peeling layer on its surface, and combining with the semi-cured sheet for thermal pressing, the shortcomings in traditional copper foils in width and production efficiency are solved, and the thickness of copper foil and the production efficiency are improved.
Patent Information
- Application Number
- CN202410214555.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-27
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-02-27
AI Technical Summary
Traditional calendered copper foils have shortcomings in width and production efficiency, and the lower limit of their thickness is 9 μm, making it difficult to achieve lower thickness copper foil production and cannot meet the extremely thinning needs of electronic devices.
Through technical means such as polymer film pretreatment and physical vapor deposition, a thin copper layer is deposited and a barrier layer and a peeling layer are formed on its surface. The semi-cured sheet is combined for thermal pressing to achieve the production of flexible copper clad plates and peelable carrier copper foil.
It improves production efficiency, realizes the reduction of copper foil thickness, and can synchronize the production of flexible copper clad plates and extremely thin carrier copper foils, improving material utilization and production flexibility.
Smart Images

Figure CN118042723B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electronic circuit material processing, in particular to a production method of a flexible copper-clad laminate and a peelable copper foil with a carrier. Background Art
[0002] The trend of thinning and lightening of consumer electronics has put forward new and higher requirements on the space and structure of devices. Under certain conditions, traditional rigid circuit boards cannot fully meet the miniaturization requirements of devices. Flexible circuit boards (FPCs) with bendable properties can perfectly solve the problems of device miniaturization and unconventional spatial layout. Flexible copper clad laminates (FCCLs) are indispensable raw materials for the production of flexible FPCs. High molecular polymers represented by polyimide (PI), modified polyimide (MPI), thermosetting polyimide (TPI) and polyethylene terephthalate (PET) and their derivatives have excellent flexibility (bending resistance) and are widely used in FCCL. As the raw material that provides conductivity in FCCL, the performance of copper foil will also have a decisive effect on the overall performance of FCCL and FPC. Rolled copper foil has a flat crystal structure and exhibits excellent flexibility under stress, and is widely used in the fields of FCCL and FPC. Electrolytic copper foil uses chemical copper as raw material to form single copper through electrochemical reduction. There are obvious differences in microscopic crystal structure from rolled copper foil, and there are also some differences in macroscopic performance. It should be pointed out that the rolled copper foil is limited by the processing capacity of the processing equipment, and there is room for optimization in terms of width and production efficiency. For example, the width of conventional rolled copper foil is usually no more than 1000mm, while the width of electrolytic copper foil depends on the width of the titanium cathode roller and can usually reach 1350mm or 1500mm. In addition, rolled copper foil is processed with copper ingots as raw materials, and multiple high-temperature and high-pressure treatments are required during the production process, and the production efficiency and capacity are relatively low. Electrolytic copper foil uses copper wire, copper plate or copper rod as raw materials to generate copper sulfate through chemical reaction with sulfuric acid and oxygen, and undergoes oxidation-reduction reaction under the action of direct current to generate single copper. It has greater advantages in production efficiency and capacity than rolled copper foil. In addition to rolled copper foil and electrolytic copper foil, copper deposition by physical vapor deposition (PVD) has also received increasing attention in recent years.
[0003] In addition to optimizing the connection, the demand for ultra-thin electronic devices can also be achieved by reducing the thickness of the circuit board itself. Advanced electronic circuit device processing technology represented by high-density interconnect (HDI) has been rapidly developed and popularized in recent years. Against the background of increasingly high requirements for thinning of boards, reducing the thickness of raw materials has become the mainstream trend of development. Restricted by the production and processing methods, the lower limit of the thickness of traditional electronic circuit copper foil is 9μm. To further reduce the thickness of electronic circuit copper foil, it is necessary to use metal foil or polymer film with relatively high processability as a carrier. On the basis of the carrier layer, an extremely thin copper layer with a thickness of no more than 5μm is produced. The reduction in the thickness of the copper layer is not only of positive significance to the processability of the downstream, but also can effectively reduce the thickness of the circuit board, achieve the thinning of the board and reduce the size of the device. Summary of the invention
[0004] In view of the deficiencies of the prior art, the present invention provides a method for producing a flexible copper-clad laminate and a peelable copper foil with a carrier, which solves the problems mentioned in the above background technology.
[0005] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for producing a flexible copper-clad laminate and a peelable copper foil with a carrier, specifically comprising the following steps:
[0006] S01. Polymer film pretreatment: bombarding the surface of the polymer film with plasma to activate the surface of the polymer film and enhance the bonding force between the polymer film and the film layer to be deposited;
[0007] S02. Deposition of a first ultra-thin copper layer: metalizing the surface of the polymer film by physical vapor deposition, and then thickening the metallized film by physical vapor deposition, electrochemical deposition or chemical deposition to generate a first ultra-thin copper layer;
[0008] S03, first barrier layer deposition: forming a barrier layer composed of titanium, iron, nickel, cobalt, molybdenum or graphene on the surface of the first ultra-thin copper layer by physical vapor deposition, chemical deposition or electrochemical deposition;
[0009] S04, stripping layer deposition: forming a stripping layer composed of amorphous carbon (AC), diamond-like carbon (DLC), graphene or titanium on the surface of the first barrier layer by physical vapor deposition, chemical deposition, or electrochemical deposition;
[0010] S05. Deposition of a second barrier layer: forming a barrier layer composed of titanium, iron, nickel, cobalt, molybdenum or graphene on the surface of the first ultra-thin copper layer by physical vapor deposition, chemical deposition or electrochemical deposition;
[0011] S06. Deposition of a second ultra-thin copper layer: depositing an ultra-thin copper layer with a thickness of 1.5-3.0 μm on the surface of the second barrier layer by physical vapor deposition or electrochemical deposition;
[0012] S07, second ultra-thin copper layer-prepreg lamination: select a prepreg with a resin system of BT or BT-like and laminate it with the second ultra-thin copper layer, and then press the copper clad laminate;
[0013] S08. Separation of copper clad laminate: Under a certain mechanical force, the copper clad laminate formed by pressing the second ultra-thin copper layer and the prepreg is separated from the flexible copper clad laminate formed by the polymer film in the middle part - the first ultra-thin copper layer.
[0014] Preferably, the polymer used in the polymer film pretreatment in step S01 is polyimide PI or polyethylene terephthalate PET, and the thickness of the polymer film is between 3-5 mils;
[0015] Preferably, in step S01, oxygen plasma or argon plasma is used to simultaneously activate the upper and lower surfaces of the polymer film during the pretreatment of the polymer film, and the vacuum degree during the pretreatment is not less than 2.0×10 -4 Pa, pretreatment time is not less than 30min, pretreatment power is 2-10kW.
[0016] Preferably, the deposition of the first ultra-thin copper layer on the pre-treated polymer surface in step S02 can be achieved directly by a one-step physical vapor deposition (PVD) method, or by a two-step method in which the polymer film surface is first metallized by PVD, and then the ultra-thin copper layer is thickened by chemical deposition or electrochemical deposition.
[0017] Preferably, in step S02, the target material used in the process of sputtering the copper layer on the surface of the pre-treated polymer is a copper target (with a purity of not less than 99.999%), and the first ultra-thin copper layer is deposited by high-power pulsed magnetron sputtering (HiPIMS).
[0018] Preferably, in step S02, the duty cycle of the first ultra-thin copper layer deposition process using one-step HiPIMS is 2-8%, the sputtering power is 15-20 kW, and the sputtering vacuum is not less than 3.0×10 -5 Pa, sputtered copper layer thickness 3-5μm.
[0019] Preferably, in step S02 , the thickness of the PVD sputtered copper layer during the deposition of the first ultra-thin copper layer using a two-step method is between 25-50 nm, and the thickness of the chemically plated copper layer is between 3-5 μm.
[0020] Preferably, in step S02, the first ultra-thin copper layer is electrochemically deposited using pulse electrochemical deposition assisted by an additive, the concentration of the additive is between 5-20 mg / L, and the average current density of the pulse current is between 800-1500 A / m 2 The duty cycle is between 25-40% and the pulse frequency is between 1000-3000Hz.
[0021] Preferably, the composition of the first barrier layer in step S03 is one or more of titanium, nickel-molybdenum alloy, and graphene, the thickness of the first barrier layer is between 10-50nm, and the deposition process of the first barrier layer can be achieved by one or more of physical vapor deposition and electrochemical deposition.
[0022] Preferably, the composition of the stripping layer in step S04 is one or more of amorphous carbon (AC), diamond-like carbon (DLC), and titanium, and the deposition process of the stripping layer can be achieved by one or more of physical vapor deposition and electrochemical deposition.
[0023] Preferably, in step S05, the second barrier layer composition is one or more of titanium, nickel-molybdenum alloy, and graphene, the thickness of the second barrier layer is between 10-50nm, and the second barrier layer deposition process can be achieved by one or more of physical vapor deposition and electrochemical deposition.
[0024] Preferably, in step S06, the second ultra-thin copper layer can be formed by physical vapor deposition or electrochemical deposition, and the thickness of the ultra-thin copper layer is between 1.5-3.0 μm.
[0025] Preferably, the type of resin used in the pressing of the second ultra-thin copper layer and the semi-cured material in step S07 is BT or BT-like, and the peel strength between the ultra-thin copper layer and the plate is not less than 4.0 lb / in.
[0026] Preferably, when the copper-clad laminates are separated in step S08, the separation force between the FCCL and the upper and lower copper-clad laminates is between 10-100 gf / cm.
[0027] Beneficial Effects
[0028] The present invention provides a method for producing a flexible copper-clad laminate and a peelable copper foil with a carrier. Compared with the prior art, the present invention has the following beneficial effects:
[0029] The production method of the flexible copper-clad laminate and the peelable copper foil with carrier comprises the following steps: firstly, a polymer film is selected as a substrate, and the surface activity is improved by pre-treating the surface of the polymer film; then, a first ultra-thin copper layer is deposited on the surface of the pre-treated polymer film; then, a first barrier layer is deposited on the surface of the first ultra-thin copper layer; then, a peeling layer is deposited on the surface of the first barrier layer; then, a second barrier layer is deposited on the surface of the peeling layer; then, a second ultra-thin copper layer is deposited on the surface of the second barrier layer; then, a suitable prepreg is selected and the second ultra-thin copper layer is thermally pressed to form a copper-clad laminate; finally, the second ultra-thin copper layer is pressed with the prepreg under a certain force to form a clad laminate. The flexible copper clad laminate formed by the copper plate and the polymer film in the middle part - the first ultra-thin copper layer is separated, so that two copper clad laminates with ultra-thin copper layers and one flexible copper clad laminate can be produced at the same time, and the production efficiency is greatly improved, and the synchronous production of flexible copper clad laminate FCCL and peelable rigid copper clad laminate with copper foil attached to a carrier can be realized; the material utilization rate is significantly improved, and the polymer film is used as the raw material of the flexible copper clad laminate and the carrier of the peelable copper foil with a carrier. After supporting the normal production of the peelable copper foil with a carrier, the circuit board can continue to be produced; the production flexibility is effectively improved, and the full dry process can be selected according to the needs, and the dry-wet mixed production process can be selected according to the cost control needs. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a process flow chart of the present invention;
[0031] Figure 2 SEM images of copper foil produced with different process parameters of the present invention;
[0032] Figure 3 This is a cloud diagram of the surface profile of copper foil produced with different process parameters of the present invention. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] See also Figure 1-3 The present invention provides twelve technical solutions: specifically including the following embodiments:
[0035] Example 1
[0036] The present invention provides a production technology capable of simultaneously producing a flexible copper-clad laminate and an ultra-thin copper foil with a carrier, which specifically comprises the following steps:
[0037] S01. Polymer film pretreatment
[0038] A 5 mil thick polyimide PI film was selected as the substrate, and the upper and lower surfaces of the PI base film were simultaneously pre-treated with oxygen plasma for surface activation. The parameters during the pre-treatment process are as follows:
[0039] Vacuum degree: 2.0×10 -4 Pa
[0040] Pre-processing power: 10kW
[0041] Pretreatment time: 45min
[0042] S02, first ultra-thin copper layer deposition
[0043] The surface of the PI film is metallized by depositing an extremely thin copper layer on the pre-treated PI film surface by DC sputtering. The parameters in the deposition process of the extremely thin copper layer are as follows:
[0044] Target material: copper target (purity ≥ 99.999%)
[0045] Vacuum degree: 3.0×10 -5 Pa
[0046] Sputtering power: 10kW
[0047] After sputtering, the ultra-thin copper layer is thickened by high-power pulsed magnetron sputtering (HiPIMS) deposition. The parameters during the electrochemical thickening process are as follows:
[0048] Target material: copper target (purity ≥ 99.999%)
[0049] Vacuum degree: 1.0×10 -5 Pa
[0050] Sputtering power: 15kW
[0051] Duty cycle: 5%
[0052] S03, first barrier layer deposition
[0053] The first barrier layer is deposited on the surface of the first ultra-thin copper layer by direct current sputtering. The parameters of the first barrier layer deposition process are as follows:
[0054] Target material: titanium target (purity ≥ 99.999%)
[0055] Vacuum degree: 2.0×10 -5 Pa
[0056] Sputtering power: 5kW
[0057] Processing time: 60s
[0058] S04, peeling layer deposition
[0059] The peeling layer is deposited on the surface of the first-pole barrier layer by HiPIMS sputtering. The parameters of the peeling layer deposition process are as follows:
[0060] Target material: carbon target (purity ≥ 99.999%)
[0061] Vacuum degree: 1.0×10 -5 Pa
[0062] Sputtering power: 15kW
[0063] Duty cycle: 8%
[0064] Processing time: 120s
[0065] S05, second pole barrier layer deposition
[0066] The second barrier layer is deposited on the surface of the peeling layer by DC sputtering. The parameters during the deposition of the second barrier layer are as follows:
[0067] Target material: titanium target (purity ≥ 99.999%)
[0068] Vacuum degree: 2.0×10 -5 Pa
[0069] Sputtering power: 5kW
[0070] Processing time: 60s
[0071] S06, second ultra-thin copper layer deposition
[0072] The second ultra-thin copper layer is deposited on the surface of the second barrier layer by high power pulsed magnetron sputtering (HiPIMS). The parameters during the deposition of the second ultra-thin copper layer are as follows:
[0073] Target material: copper target (purity ≥ 99.999%)
[0074] Vacuum degree: 2.0×10 -5 Pa
[0075] Sputtering power: 15kW
[0076] Duty cycle: 2%
[0077] S07, Second Ultra-Thin Copper Layer - Semi-Pressure Lamination
[0078] The semi-cured sheet of BT resin system and the second ultra-thin copper layer are heat-pressed in a laminator. The parameters of the lamination process are as follows:
[0079] Prepreg Model: MGC832NXA
[0080] Lamination temperature: 240℃
[0081] Insulation time: 140min
[0082] Pressure per unit area: 30kgf / m 2
[0083] S08, copper clad laminate separation
[0084] Use a vacuum suction cup to fix the copper clad laminate laminated in step S07, and apply force in the opposite direction to separate the copper clad laminate laminated by the second ultra-thin copper layer and the prepreg from the flexible copper clad laminate formed by the polymer film in the middle part - the first ultra-thin copper layer. The parameters in the copper clad laminate separation process are as follows:
[0085] Washing plate vacuum degree: 2.0×10 -3 Pa
[0086] Suction cup moving speed: 5.0cm / min
[0087] Example 2
[0088] The difference between this embodiment and embodiment 1 is that the parameters in the S01 polymer film pretreatment process are adjusted. The parameters in the polymer film pretreatment process are as follows:
[0089] Polymer name: Polyethylene terephthalate PET
[0090] Film thickness: 5mil
[0091] Treatment agent: Argon plasma
[0092] Vacuum degree: 1.0×10 -4 Pa
[0093] Pre-processing power: 2kW
[0094] Pretreatment time: 60min
[0095] Example 3
[0096] The difference between this embodiment and embodiment 1 is that the deposition method of the first ultra-thin copper layer of SO2 is adjusted, and the two-step deposition method of first DC sputtering and then HiPIMs thickening is adjusted to a one-step direct deposition to the designed thickness using HiPIMS. The parameters in the one-step deposition process of the first ultra-thin copper layer are as follows:
[0097] Target material: copper target (purity ≥ 99.999%)
[0098] Vacuum degree: 1.0×10 -5 Pa
[0099] Sputtering power: 20kW
[0100] Duty cycle: 2%
[0101] Deposition time: 30min
[0102] Example 4
[0103] The difference between this embodiment and embodiment 1 is that the deposition method of the first ultra-thin copper layer of SO2 is adjusted, and the two-step deposition method of first DC sputtering to lay the base layer and then thickening by HiPIMs is adjusted to first DC sputtering to lay the base layer and then thickening by pulse electrochemical deposition assisted by additives. The specific parameters of additive-assisted pulse electrochemical copper deposition are as follows:
[0104] Cu 2+ Ion concentration: 80g / L
[0105] H2SO4 concentration: 120g / L
[0106] Additive concentration: 5mg / L
[0107] Average current density: 800A / m 2
[0108] Duty cycle: 25%
[0109] Pulse frequency: 3000Hz
[0110] Deposition time: 180s
[0111] Example 5
[0112] The difference between this embodiment and embodiment 1 is that the deposition method of the first ultra-thin copper layer of SO2 is adjusted, and the base layer is firstly formed by direct current sputtering and then thickened by pulse electrochemical deposition assisted by additives. The specific parameters of the additive-assisted pulse electrochemical copper deposition are as follows:
[0113] Cu 2+ Ion concentration: 80g / L
[0114] H2SO4 concentration: 120g / L
[0115] Additive concentration: 20mg / L
[0116] Average current density: 800A / m 2
[0117] Duty cycle: 25%
[0118] Pulse frequency: 1000Hz
[0119] Deposition time: 180s
[0120] Example 6
[0121] The difference between this embodiment and embodiment 1 is that the relevant parameters in the deposition process of the first barrier layer of SO3 are adjusted, and the direct current sputtering of titanium is adjusted to electrochemical deposition of graphene. The parameters in the electrochemical deposition of graphene are as follows:
[0122] Graphene oxide concentration: 1.0g / L
[0123] Electrolyte temperature: 30°C
[0124] Average current density: 15A / m2
[0125] Duty cycle: 33%
[0126] Pulse frequency: 1000Hz
[0127] Electrodeposition time: 300s
[0128] Example 7
[0129] The difference between this embodiment and embodiment 1 is that the relevant parameters in the deposition process of the first barrier layer of SO3 are adjusted, and the direct current sputtering of titanium is adjusted to the electrochemical deposition of nickel-molybdenum alloy. The parameters in the electrochemical deposition process of nickel-molybdenum alloy are as follows:
[0130] Ni 2+ Ion concentration: 1.0g / L
[0131] Mo(VI) concentration: 0.33g / L
[0132] Complexing agent concentration: 45g / L
[0133] Electrolyte pH: 10.25
[0134] Average current density: 25A / m2
[0135] Duty cycle: 40%
[0136] Pulse frequency: 200Hz
[0137] Electrodeposition time: 60s
[0138] Example 8
[0139] The difference between this embodiment and embodiment 1 is that the relevant parameters in the SO4 stripping layer deposition process are adjusted, and the HiPIMS deposition of amorphous carbon is adjusted to DC sputtering of titanium. The parameters in the DC sputtering of titanium stripping layer are as follows:
[0140] Target material: titanium target (purity ≥ 99.999%)
[0141] Vacuum degree: 1.5×10 -5 Pa
[0142] Sputtering power: 10kW
[0143] Processing time: 120s
[0144] Example 9
[0145] The difference between this embodiment and embodiment 1 is that the relevant parameters in the SO4 peeling layer deposition process are adjusted, and the HiPIMS deposition of amorphous carbon is adjusted to the HiPIMS deposition of diamond-like carbon DLC. The parameters in the DLC peeling layer deposition process are as follows:
[0146] Target material: carbon target (purity ≥ 99.999%)
[0147] Vacuum degree: 1.0×10 -5 Pa
[0148] Sputtering power: 20kW
[0149] Duty cycle: 2%
[0150] Processing time: 120s
[0151] Example 10
[0152] The difference between this embodiment and embodiment 1 is that the relevant parameters in the deposition process of the second barrier layer S05 are adjusted, and the DC sputtering titanium layer is adjusted to the DC sputtering nickel-molybdenum alloy. The parameters in the DC sputtering nickel-molybdenum alloy process are as follows:
[0153] Target: Nickel-molybdenum alloy target (nickel content 75at%, molybdenum content 25at%)
[0154] Vacuum degree: 1.5×10 -5 Pa
[0155] Sputtering power: 10kW
[0156] Processing time: 180s
[0157] Embodiment 11
[0158] The difference between this embodiment and embodiment 1 is that the relevant parameters in the deposition process of the second ultra-thin copper layer of S06 are adjusted, and the HiPIMS sputtering deposition is adjusted to the pulse electrochemical deposition assisted by additives. The parameters in the pulse electrochemical copper deposition process assisted by additives are as follows:
[0159] Cu 2+ Ion concentration: 80g / L
[0160] H2SO4 concentration: 120g / L
[0161] Additive concentration: 15mg / L
[0162] Average current density: 120A / m 2
[0163] Duty cycle: 33%
[0164] Pulse frequency: 12000Hz
[0165] Deposition time: 180s
[0166] Example 12
[0167] The difference between this embodiment and embodiment 1 is that the relevant parameters in the deposition process of the second ultra-thin copper layer S06 are adjusted, and the one-step HiPIMS sputtering deposition is adjusted to first DC sputtering to lay the base layer and then thicken it with the help of additive-assisted pulse electrochemical deposition. The parameters in the deposition process of the second ultra-thin copper layer are as follows:
[0168] Target material: copper target (purity ≥ 99.999%)
[0169] Vacuum degree: 3.0×10 -5 Pa
[0170] Sputtering power: 10kW
[0171] Processing time: 30min
[0172] Cu 2+ Ion concentration: 80g / L
[0173] H2SO4 concentration: 120g / L
[0174] Additive concentration: 15mg / L
[0175] Average current density: 100A / m 2
[0176] Duty cycle: 25%
[0177] Pulse frequency: 2000Hz
[0178] Deposition time: 150s
[0179] Comparative Example 1
[0180] The difference between this comparative example and Example 1 is that the electrolytic copper foil is prepared by an electrochemical deposition method, and then the electrolytic copper foil and the PI base film are hot pressed by a roll-to-roll method to prepare a flexible copper clad laminate.
[0181] Copper foil thickness: 12μm
[0182] PI base film thickness: 5mil
[0183] Lamination temperature: 370℃
[0184] Comparative Example 2
[0185] The difference between this comparative example and Example 1 is that a barrier layer, a peeling layer, an ultra-thin copper layer, a micro-roughening layer, an anti-rust layer, and a chemical bonding layer are sequentially prepared on the electrolytic copper foil by electrochemical deposition to form an ultra-thin copper foil with a carrier.
[0186] Carrier copper layer thickness: 18μm
[0187] Carrier copper layer surface roughness Rz: 1.2μm
[0188] Barrier layer thickness: 1.0nm
[0189] Ultra-thin copper layer thickness: 3.0μm
[0190] Comparative Example 3
[0191] The difference between this comparative example and Example 1 is that a peeling layer, an ultra-thin copper layer, a micro-roughening layer, and an anti-rust layer are sequentially prepared on the PI base film by physical vapor deposition to form an ultra-thin copper foil with a carrier.
[0192] PI base film thickness: 18μm
[0193] Stripping layer thickness: 2.5nm
[0194] Ultra-thin copper layer thickness: 2.0μm
[0195] In order to more intuitively reflect the implementation effect of the present invention, the differences in physical properties between different embodiments and comparative examples were compared and studied with the help of a scanning electron microscope (SEMTescanVEGA3), a laser confocal microscope (Olympus, OLS5100), a peel strength tester and a separation force tester. Figure 2 Shown are SEM images of the extremely thin copper layers of the flexible copper clad laminates produced in Example 1 and Comparative Example 1 ((a) Example 1; (b) Comparative Example 1). The effect of the growth method on the microscopic morphology of the copper foil can be clearly observed from the figure. The copper layer grown using physical vapor deposition is relatively dense, while the copper foil produced by electrochemical deposition is relatively loose. The difference in density in the microscopic morphology may be due to the rate during the growth of the copper foil. During physical vapor deposition, copper atoms escape from the target material to the substrate under the bombardment of plasma and the growth rate is relatively slow, while during electrochemical deposition, copper ions obtain electrons under the action of the electric field and are reduced to copper atoms, and the growth rate is relatively fast.
[0196] Figure 3The surface contour cloud map of the ultra-thin copper layer with a carrier produced according to the parameters of Example 1 and Comparative Example 1 is shown ((a) Example 1; (b) Comparative Example 1). The laser confocal surface contour cloud map can intuitively reflect the distribution of the surface contour of the copper foil. In the figure, the surface contour of the blue and green areas is relatively low, and the surface contour of the red area is relatively high. Figure 3 The color shown in (a) is mainly green, indicating that the surface profile of the copper foil is low, and the green distribution is relatively uniform, indicating that the surface profile of the copper foil produced under this process condition is relatively stable. Figure 3 (b) shows the characteristics of alternating distribution of yellow, green and blue, indicating that the surface profile of the copper foil produced under this process condition has a certain degree of fluctuation.
[0197] The peel strength between the copper layer and the dielectric material is an important indicator to ensure the reliability of the copper clad laminate in downstream processing and terminal application. Table 1 summarizes the peel strength of samples produced with different process parameters and the separation force required for the copper clad laminates to separate from each other. From the data shown in the table, it can be seen that the type of base film in the flexible copper clad laminate has a significant effect on the peel strength, and the bonding force between the PI base film and the copper layer is slightly higher than the bonding force between the PET base film and the copper layer. The separation force after the carrier copper foil and BT resin are pressed together is relatively stable, and the peel strength of the extremely thin copper foil with a thickness of 3μm and BT resin after pressing is close to 4.0lb / in. Stable bonding force is conducive to improving the reliability of the carrier copper foil during downstream processing and use.
[0198] Table-1. Comparison of physical properties of products produced in different examples and comparative examples
[0199]
[0200]
[0201]
[0202] Finally, it should be emphasized that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
[0203] Meanwhile, the contents not described in detail in this specification belong to the prior art known to those skilled in the art.
[0204] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0205] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for producing a flexible copper-clad laminate and a peelable copper foil with a carrier, characterized in that: The specific steps include: S01. Polymer film pretreatment: bombarding the surface of the polymer film with plasma to activate the surface of the polymer film and enhance the bonding force between the polymer film and the film layer to be deposited; S02, deposition of a first ultra-thin copper layer: metalizing the upper and lower surfaces of the polymer film by physical vapor deposition, and then thickening the metalized film by physical vapor deposition, electrochemical deposition or chemical deposition to generate a first ultra-thin copper layer; S03, first barrier layer deposition: forming a barrier layer composed of titanium, iron, nickel, cobalt, molybdenum or graphene on the surface of the first ultra-thin copper layer by physical vapor deposition, chemical deposition or electrochemical deposition; S04, stripping layer deposition: forming a stripping layer composed of amorphous carbon, diamond-like carbon, graphene or titanium on the surface of the first barrier layer by physical vapor deposition, chemical deposition or electrochemical deposition; S05. Deposition of a second barrier layer: forming a barrier layer composed of titanium, iron, nickel, cobalt, molybdenum or graphene on the surface of the peeling layer by physical vapor deposition, chemical deposition or electrochemical deposition; S06. Deposition of a second ultra-thin copper layer: depositing an ultra-thin copper layer with a thickness of 1.5-3.0 μm on the surface of the second barrier layer by physical vapor deposition or electrochemical deposition; S07, second ultra-thin copper layer-prepreg lamination: select a prepreg with a resin system of BT or BT-like and laminate it with the second ultra-thin copper layer, and then press the copper clad laminate; S08, copper clad laminate separation: the copper clad laminate formed by laminating the second ultra-thin copper layer and the prepreg is separated from the flexible copper clad laminate formed by the polymer film-first ultra-thin copper layer in the middle part under a certain mechanical force; The polymer used in the polymer film pretreatment in step S01 is polyimide PI or polyethylene terephthalate PET, and the thickness of the polymer film is between 3-5 mils; oxygen plasma or argon plasma is used in the polymer film pretreatment to simultaneously activate the upper and lower surfaces of the polymer film, and the vacuum degree during the pretreatment process is not less than 2.0×10 -4 Pa, pretreatment time is not less than 30min, pretreatment power is 2-10kW; In step S02, the target material used in the process of sputtering the copper layer on the surface of the pretreated polymer is a copper target, and the first ultra-thin copper layer is deposited by high-power pulsed magnetron sputtering; In step S02, during the electrochemical deposition of the first ultra-thin copper layer, pulse electrochemical deposition assisted by an additive is used, the concentration of the additive is between 5-20 mg / L, and the average current density of the pulse current is between 800-1500 A / m 2 The duty cycle is between 25-40%, and the pulse frequency is between 1000-3000Hz; In step S03, the thickness of the first barrier layer is between 10-50 nm; In step S05, the thickness of the second barrier layer is between 10-50 nm.
2. The method for producing a flexible copper-clad laminate and a peelable copper foil with a carrier according to claim 1, characterized in that: The type of resin used in the second ultra-thin copper layer-semi-cured lamination in step S07 is BT or BT-like, and the peel strength between the ultra-thin copper layer and the plate is not less than 4.0 lb / in.
3. The method for producing a flexible copper-clad laminate and a peelable copper foil with a carrier according to claim 1, characterized in that: When the copper clad laminates are separated in step S08, the separation force between the flexible copper clad laminate and the upper and lower copper clad laminates is between 10-100 gf / cm.
Citation Information
Patent Citations
Metal foil with carrier and preparation method thereof
US20210392749A1